Chagas Disease : Synthetic Studies Towards Target Identification and Potential Treatment - Miladinovic,Kristian (2025)
Introduction: Chagas disease, caused by Trypanosoma cruzi, remains a significant public health challenge, particularly among socioeconomically disadvantaged populations in developing countries. Although two drugs are currently available, their use is associated to severe side effects, and they are only widely accepted as a treatment against the acute phase of the disease. Background: A Waltherione F derivative with promising potency (IC50: 6 nm), was recently synthesized at RG discovery. Identifying the target of the Waltherione F like compounds is of great interest as it would allow for in silico techniques, significantly accelerating the drug discovery process. The recently published photoproximity labelling method was chosen as the preferred approach, although it requires the synthesis of multiple chemical components. Aim(s): The primary aim of this thesis is to synthesize a component for the photoproximity labelling, namely a ligand that has affinity for the Waltherione F target and can be attached to a Boc-PEG3 moiety. Several analogues of the promising Waltherione F derivative will also be synthesized with the aim of further investigate the structure-activity relationship and improving solubility. Methods: The Conrad Limpach synthesis will be employed for constructing quinoline scaffolds. Position 3 of the quinoline ring will be functionalized by substituting ethyl acetoacetate at position 2, prior to cyclization. Results: The ligand for photo proximity labelling has been successfully synthesized however, the Boc-PEG3 moiety could not be attached due to time constraints. Four analogues of promising Waltherione F derivatives have been synthesized. Potency cannot yet be reported, as results from biological testing remain pending. Conclusion: Introducing substituents at position 2 of ethyl acetoacetate, prior to cyclization, has proven to be a versatile and reliable method for accessing previously synthetically unachievable compounds. Additional work is required for attaching the Boc-PEG3 moiety to the photoaffinity ligand
Keywords: Chagas Disease; Conrad Limpach reaction; Trypanosoma cruzi; Quinoline; Waltherione F; Organic Chemistry